A novel mutation in PIGW causes glycosylphosphatidylinositol deficiency without hyperphosphatasia. Issue 12 (14th September 2016) - Hogrebe, Max; Murakami, Yoshiko; Wild, Martin; Ahlmann, Martina; Biskup, Saskia; Hörtnagel, Konstanze; Grüneberg, Marianne; Reunert, Janine; Linden, Tobias; Kinoshita, Taroh; Marquardt, Thorsten
Abstract : In recent years, many mutations have been identified that affect the biosynthesis of the glycosylphosphatidylinositol anchor, a biomolecule that attaches surface molecules to cell membranes. Here, we present two second‐degree cousins with unexplained patterns of seizures. Next‐generation sequencing identified the homozygous c.460A>G; p.(R154G) PIGW mutation in both patients. Transfection of the mutated allele into Pigw ‐defective CHO cells indicated impaired enzymatic activity of the mutated PIGW product. Alkaline phosphatase did not exceed the upper normal range and flow cytometry of CD16, CD24, and CD66c on granulocytes showed subtle changes of the cellular expression of the glycosylphosphatidylinositol‐anchored proteins. The patients' phenotype is therefore remarkably different from the phenotype of the only other described individual with PIGW mutations. Patients might therefore be missed when relying on traditional flow cytometry of glycosylphosphatidylinositol‐anchored proteins only and we suggest that glycosylphosphatidylinositol‐deficiency should be considered even with patients not showing the typical clinical phenotypes. © 2016 Wiley Periodicals, Inc.